Penggunaan Frasa Adjektival dan Frasa Preposisional pada Teks Berita Daring Tempo.com Terbitan Agustus 2025 - Devita Nur Hadiyani; Dika Rosyiiddien Suryana; Eqy Wahyu Ramadhani; Naili Nazilatur Rohmah; Siti Mutmainah; Asep Purwo Yudi Utomo; Hafiz Rafi Uddin; Ikvina Hasanatika (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
This research is motivated by the importance of phrase analysis in syntactic studies for understanding the structure and relationships among components within Indonesian sentences. As grammatical units, phrases play a strategic role in shaping meaning, so they should be examined in terms of their constituent elements and their functions in the text. This study aims to analyze the use of adjectival phrases and prepositional phrases found in news texts. The method used is a qualitative descriptive method with observing and note-taking techniques, supported by a syntactic theoretical approach. The findings show that there are twenty-five adjectival phrases and sixty-eight prepositional phrases identified in five news texts published on Tempo.com in August 2025. “lebih cepat” is one example of an adjectival phrase found in the texts, while “ke arah pendemo” is an example of a prepositional phrase. These findings indicate that Indonesian phrases have systematic formation patterns and complementary syntactic functions. This research serves as a useful reference for the development of syntactic studies, linguistic learning, and the analysis of phrase usage in various language contexts.